2012
DOI: 10.1002/ajh.23193
|View full text |Cite
|
Sign up to set email alerts
|

Chronic eosinophilic leukemia‐not otherwise specified has a poor prognosis with unresponsiveness to conventional treatment and high risk of acute transformation

Abstract: Chronic eosinophilic leukemia-not otherwise specified (CEL-NOS) is a rare disorder with hypereosinophilia and an increased number of blood or marrow blast (<20%) or an evidence of eosinophil clonality. We evaluated the clinical outcome of 10 patients with CEL-NOS. Seven males and three females at a median age of 62 years (range, 23-73) were included. The median leukocyte count at diagnosis was 33.4 3 10 9 /l (range, 9.3-175.0) with a median eosinophil count of 15.6 3 10 9 /l (range, 1.5-136.0). Median hemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
91
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 20 publications
4
91
1
Order By: Relevance
“…In our study, chronic eosinophilic leukemia, not otherwise specified patients had a median disease-specific survival of 14.4 months, and three cases progressed to acute myeloid leukemia or accelerated phase. Our findings are similar to those reported by Helbig and colleagues 27 and suggest that chronic eosinophilic leukemia, not otherwise specified is a clinically aggressive disease, often resistant to therapy, with a relatively high rate of acute myeloid leukemia transformation and a short survival. In contrast, idiopathic hypereosinophilic syndrome patients with no identifiable mutations presented with hypereosinophilia at a much younger age than chronic eosinophilic leukemia, not otherwise specified, and had more frequent symptoms associated with eosinophil activation, such as dermatological, pulmonary, gastrointestinal, and rheumatologic manifestations, as has been reported by others.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, chronic eosinophilic leukemia, not otherwise specified patients had a median disease-specific survival of 14.4 months, and three cases progressed to acute myeloid leukemia or accelerated phase. Our findings are similar to those reported by Helbig and colleagues 27 and suggest that chronic eosinophilic leukemia, not otherwise specified is a clinically aggressive disease, often resistant to therapy, with a relatively high rate of acute myeloid leukemia transformation and a short survival. In contrast, idiopathic hypereosinophilic syndrome patients with no identifiable mutations presented with hypereosinophilia at a much younger age than chronic eosinophilic leukemia, not otherwise specified, and had more frequent symptoms associated with eosinophil activation, such as dermatological, pulmonary, gastrointestinal, and rheumatologic manifestations, as has been reported by others.…”
Section: Discussionsupporting
confidence: 92%
“…The case was classified as acute common lymphoblastic leukemia (LLA), developed from a chronic eosinophilic leukemia not otherwise specified (CEL-NOS). Although acute transformation has already been described as a possible clinical outcome for CEL-NOS, LLA transformation has rarely been reported [1]. Primary eosinophilias encompass a group of hematologic disorders with potential for end-organ damage and acute transformation.…”
mentioning
confidence: 99%
“…In cases of CEL where the RT-PCR for FIP1L1-PDGFRA is negative or unknown, the prognosis is poor, being unresponsive or short lived to imatinib [25], conventional therapy [26] and has a high rate of acute transformation [26]. However, it has been reported that approximately 40% of patients who response to imatinib are negative for the FIP1L1-PDGFRA fusion protein, although doses as high as 600mg/day may not be effective [27].…”
mentioning
confidence: 99%
“…The complete response rate has been reported as 24% compared with 98% of cases which were FIP1L1-PDGFRA positive [16]. However, hematological responses are often partial and short lived [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation